2019
DOI: 10.1016/j.ijmecsci.2019.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling of the high-velocity impact of autoclaved aerated concrete (AAC) blocks and some experimental results

Abstract: Highlight  High velocity impact behavior of Autoclaved aerated concrete (AAC) was studied.  An analytical model was presented to predict the residual velocity of projectile.  Four energy absorption mechanism considered to predict impact behavior accurately.  The model validated by comparison of model results with those of experiments.  The validated model was employed for parametric study and sensitivity analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…They also investigated the ballistic limit velocity of AAC targets under the influence of rigid projectiles. The results showed that the introduced analytical model was in good agreement with the experimental results [18].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…They also investigated the ballistic limit velocity of AAC targets under the influence of rigid projectiles. The results showed that the introduced analytical model was in good agreement with the experimental results [18].…”
Section: Introductionsupporting
confidence: 73%
“…They also tested several reduced-scale structures with AAC walls on the shaking table [17]. In a study conducted by Bayat et al [18], the behavior of AAC blocks under severe impulse loads was analyzed. They also investigated the ballistic limit velocity of AAC targets under the influence of rigid projectiles.…”
Section: Introductionmentioning
confidence: 99%
“…Hard armors have been used to protect against high-velocity projectiles. A complex process of fracture occurs during perforation of hard armor that have been investigated a lot during the last few decades [2][3][4][5][6]. Metals have been the primary materials used for ballistic applications due to the high hardness and tensile strength [2,7,8].…”
Section: Introductionmentioning
confidence: 99%